- #1
DivGradCurl
- 372
- 0
Folks,
I'm reading the 3rd edition of Thin Film Optical Filters by Macleod, and I've derived his expression for phase shift upon reflection (page 45). Finally, it lead me to a question. Any help is highly appreciated!
[tex]\rm E_i + E_r = E_t \qquad (1)[/tex]
[tex]\rm H_i - H_r = H_t \qquad (2)[/tex]
Rewrite (2) using the definition of tilted optical admittance:
[tex]\rm \eta_0 E_i - \eta_0 E_r = \eta_1 E_t \qquad (3)[/tex]
Substitute (1) into (3):
[tex]\rm \eta_0 E_i - \eta_0 E_r = \eta_1 \left( E_i + E_r \right) \qquad (4)[/tex]
Rearrange (4):
[tex]\rm E_i \left( \eta_0 - \eta_1 \right) = E_r \left( \eta_0 + \eta_1 \right) \qquad (5)[/tex]
Apply the definition of reflection coefficient [tex]\rho[/tex]:
[tex] \rho \equiv \rm \frac{E_r}{E_i} = \frac{ \eta_0 - \eta_1}{ \eta_0 + \eta_1} \qquad (6)[/tex]
Replace [tex]\eta_1[/tex] by the input optical admittance [tex]Y[/tex] in (6):
[tex] \rho = \frac{ \eta_0 - Y}{ \eta_0 + Y} \qquad (7)[/tex]
By definition, [tex]Y \equiv C/B[/tex]. Then
[tex]\rho = \frac{ \eta_0 - C/B}{ \eta_0 + C/B} = \frac{ \eta_0 B - C}{ \eta_0 B + C} \qquad (8)[/tex]
From the general form of the characteristic matrix
[tex]\begin{bmatrix}
\displaystyle B \\
\displaystyle C
\end{bmatrix} =
\begin{bmatrix}
\displaystyle \alpha & \displaystyle i\beta \\
\displaystyle i\gamma & \displaystyle \delta
\end{bmatrix}
\begin{bmatrix}
\displaystyle 1 \\
\displaystyle \eta_m
\end{bmatrix} =
\begin{bmatrix}
\displaystyle \alpha + i\beta \eta _m \\
\displaystyle \delta \eta_m + i \gamma
\end{bmatrix} \qquad (9)
[/tex]
let [tex]B = \alpha + i\beta \eta _m[/tex] and [tex]C = \delta \eta_m + i \gamma[/tex] in (8).
(problems previewing all of this latex code in one post - I'll break it up - please wait)
I'm reading the 3rd edition of Thin Film Optical Filters by Macleod, and I've derived his expression for phase shift upon reflection (page 45). Finally, it lead me to a question. Any help is highly appreciated!
[tex]\rm E_i + E_r = E_t \qquad (1)[/tex]
[tex]\rm H_i - H_r = H_t \qquad (2)[/tex]
Rewrite (2) using the definition of tilted optical admittance:
[tex]\rm \eta_0 E_i - \eta_0 E_r = \eta_1 E_t \qquad (3)[/tex]
Substitute (1) into (3):
[tex]\rm \eta_0 E_i - \eta_0 E_r = \eta_1 \left( E_i + E_r \right) \qquad (4)[/tex]
Rearrange (4):
[tex]\rm E_i \left( \eta_0 - \eta_1 \right) = E_r \left( \eta_0 + \eta_1 \right) \qquad (5)[/tex]
Apply the definition of reflection coefficient [tex]\rho[/tex]:
[tex] \rho \equiv \rm \frac{E_r}{E_i} = \frac{ \eta_0 - \eta_1}{ \eta_0 + \eta_1} \qquad (6)[/tex]
Replace [tex]\eta_1[/tex] by the input optical admittance [tex]Y[/tex] in (6):
[tex] \rho = \frac{ \eta_0 - Y}{ \eta_0 + Y} \qquad (7)[/tex]
By definition, [tex]Y \equiv C/B[/tex]. Then
[tex]\rho = \frac{ \eta_0 - C/B}{ \eta_0 + C/B} = \frac{ \eta_0 B - C}{ \eta_0 B + C} \qquad (8)[/tex]
From the general form of the characteristic matrix
[tex]\begin{bmatrix}
\displaystyle B \\
\displaystyle C
\end{bmatrix} =
\begin{bmatrix}
\displaystyle \alpha & \displaystyle i\beta \\
\displaystyle i\gamma & \displaystyle \delta
\end{bmatrix}
\begin{bmatrix}
\displaystyle 1 \\
\displaystyle \eta_m
\end{bmatrix} =
\begin{bmatrix}
\displaystyle \alpha + i\beta \eta _m \\
\displaystyle \delta \eta_m + i \gamma
\end{bmatrix} \qquad (9)
[/tex]
let [tex]B = \alpha + i\beta \eta _m[/tex] and [tex]C = \delta \eta_m + i \gamma[/tex] in (8).
(problems previewing all of this latex code in one post - I'll break it up - please wait)